2003
DOI: 10.1046/j.1540-8183.2003.01006.x
|View full text |Cite
|
Sign up to set email alerts
|

ASD Closure with the Amplatzer Device

Abstract: We report the safety and efficacy of the Amplatzer device for transcatheter closure of ASD and fenestrated Fontan in children and adults. One hundred and two patients underwent transcatheter occlusion of the defect. The median age of the patients was 18.2 years, the median size of the ASDs by TEE was 17.6 mm, the median balloon-stretched diameter was 19.9 mm, and the median size of the device implanted was 20 mm. Immediately after the release of the device, color Doppler echocardiography revealed no residual s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…The Amplatzer Septal Occluder (AGA Medical Corp.) was the first device to receive approval from the US Food and Drug Administration for clinical use in ASD II. Initial human use was reported in 1997 with closure rates greater than 98% and implantation rates of more than 95% 3,4 …”
Section: Discussionmentioning
confidence: 99%
“…The Amplatzer Septal Occluder (AGA Medical Corp.) was the first device to receive approval from the US Food and Drug Administration for clinical use in ASD II. Initial human use was reported in 1997 with closure rates greater than 98% and implantation rates of more than 95% 3,4 …”
Section: Discussionmentioning
confidence: 99%
“…The procedure is safe, effective and reproducible in different hands, even for patients with more complex anatomies such as multifenestrated and/or aneurysmal septum, large defects and those associated with deficient rims 141516171819202122. Because children with secundum ASDs are usually asymptomatic, with normal weight gain and limited respiratory repercussion (repeat infections or wheezing, or both), the procedure is preferentially performed when the patient weighs over 20 kg.…”
Section: Outcomes After Medical Surgical or Interventional Treatmentmentioning
confidence: 99%
“…Because children with secundum ASDs are usually asymptomatic, with normal weight gain and limited respiratory repercussion (repeat infections or wheezing, or both), the procedure is preferentially performed when the patient weighs over 20 kg. Several devices have been used including the Buttoned device, Amplatzer Septal Occluder (AGA Medical, Plymouth, Minnesota, USA), Helex (WL Gore and Associates, Flagstaff, Arizona, USA) and Intrasept (Cardia, Eagan, Minnesota, USA) 141516171819202122. The experience with the CardioSEAL/Starflex/Biostar (NMT Medical, Boston, Massachusetts, USA) device has been limited in South America.…”
Section: Outcomes After Medical Surgical or Interventional Treatmentmentioning
confidence: 99%
“…A compelling review of image-guided surgical applications can be found in (Peters, 2006). There are two alternatives for minimally invasive ASD closure procedures: one using a catheter-based closure, usually under contrast-enhanced fluoroscopy (Faella et al, 2003;Papadopoulou et al, 2005); and another using rigid instruments through the chest wall (Suematsu et al, 2004), demonstrated in animals. Although clinically available, the catheter-based procedure has major disadvantages: it can only be used on a fraction of ASD (Patel et al, 2006), it excludes procedures on small children (Paragios., 2003), and it is generally performed under a high Xray dose (Papademetris et al, 2003).…”
Section: Introductionmentioning
confidence: 99%